Polyarylene sulfide resin composition and molded article
The polyarylene sulfide resin composition addresses the challenges of fluidity, burr suppression, and mold stains by optimizing non-Newtonian index, carboxyl group content, and melt flow rate, along with the use of a filler and alkoxysilane, achieving improved mechanical properties and moldability.
Patent Information
- Application Number
- JP2023120372
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
Existing polyarylene sulfide (PAS) resin compositions struggle to simultaneously achieve high fluidity during molding, effective burr suppression, and reduced mold stains while maintaining adequate adhesion and reactivity with fillers and additives.
A polyarylene sulfide resin composition is formulated with specific ranges of non-Newtonian index, carboxyl group content, cyclic content, and melt flow rate, incorporating a filler and an alkoxysilane with at least one functional group, to enhance fluidity, reduce burrs, and minimize mold stains.
The composition exhibits excellent flowability, reduced burrs, and minimized mold stains, along with improved adhesion and reactivity, resulting in enhanced mechanical properties and moldability.
Smart Images

Figure 2025017392000001 
Figure 2025017392000002 
Figure 2025017392000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyarylene sulfide resin composition which has excellent flowability and is less likely to produce burrs when formed into a molded article. [Background technology]
[0002] Polyarylene sulfide (PAS), typified by polyphenylene sulfide (PPS), has excellent properties suitable for engineering plastics, such as excellent heat resistance, gas barrier properties, moldability, chemical resistance, electrical insulation, and moist heat resistance, and is used in various electrical and electronic parts, machine parts, automotive parts, films, fibers, etc., mainly for injection molding and extrusion molding. Due to its excellent properties, PAS has been used in a wide range of applications in recent years. PAS used in these applications is required to be high molecular weight PAS for its excellent mechanical properties. In addition, there has been a strong demand for PAS that combines both flowability and burr suppression from the perspective of moldability, high functional group content from the perspective of adhesion with fillers and reactivity with additives, and low cyclic content from the perspective of reducing mold fouling and mold vent clogging.
[0003] Patent Document 1 reports a PAS resin composition that achieves high strength by increasing the molecular weight using a branching agent. As described in Patent Document 1, a resin composition consisting of PAS obtained by reacting a sulfidizing agent such as sodium sulfide with a dihalogenated aromatic compound such as p-dichlorobenzene and a polyhalogenated compound such as trichlorobenzene as a branching agent in an organic amide solvent such as N-methyl-2-pyrrolidone is reported. In addition, Patent Document 2 discloses a PAS resin that has good melt flowability and can reduce mold fouling, and Patent Document 3 discloses a method of adding highly branched PAS fine particles to linear PAS to suppress burrs. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP Patent Publication No. 02-045532 [Patent Document 2] International Publication No. 2021 / 200332 [Patent Document 3] JP 2016-108488 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the method described in Patent Document 1 has insufficient strength when obtaining a resin composition due to low adhesion to the filler and low reactivity with additives, and is also poor in suppressing burrs during molding. In addition, the method described in Patent Document 2 has good fluidity, so the molding material flows into the gaps in the mold and solidifies, which makes it easy to generate burrs. In the method described in Patent Document 3, in which highly branched PAS fine particles are added to the resin composition to suppress burrs, the adhesion and reactivity of the obtained molded product are not improved, so sufficient strength and toughness cannot be obtained. In addition, the effect of improving mold contamination during molding cannot be obtained.
[0006] As described above, the PAS resins and resin compositions described in Patent Documents 1 to 3 are unable to simultaneously solve various problems such as flowability during molding, suppression of burrs, and reduction of mold staining. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving such problems, the inventors have found that a polyarylene sulfide resin composition obtained by blending a filler and a specific alkoxysilane with a polyarylene sulfide resin having a non-Newtonian index within a specific range has excellent flowability during molding, and is excellent in suppressing burrs and reducing mold contamination, thereby completing the present invention.
[0008] That is, the present invention is as follows. 1. A polyarylene sulfide resin composition comprising 100 parts by weight of a polyarylene sulfide resin having a non-Newtonian index of 1.5 or more and 2.5 or less, a carboxyl group content of 35 μmol / g or more and 100 μmol / g or less, a cyclic content of 0.5% by weight or more and 2.0% by weight or less, and a melt flow rate measured under conditions of 315.5°C and a load of 5000 g or more and 5 g / 10 minutes or more and 300 g / 10 minutes or less, and a ... 2. The polyarylene sulfide resin composition according to 1, wherein the polyarylene sulfide resin has a dispersity expressed by weight average molecular weight / number average molecular weight of 5.5 or more and 15.0 or less. 3. The polyarylene sulfide resin composition according to 1 or 2, wherein the polyarylene sulfide resin has a weight average molecular weight of 60,000 or more and 150,000 or less. 4. A polyarylene sulfide resin composition according to any one of 1 to 3, characterized in that the polyarylene sulfide resin has a temperature-decreasing crystallization temperature (Tmc) of 190°C or higher and 230°C or lower, measured at a temperature-decreasing rate of 20°C / min using a differential scanning calorimeter (DSC). 5. A molded article made of the polyarylene sulfide resin composition according to any one of 1 to 4. Effect of the Invention
[0009] According to the present invention, it is possible to obtain a PAS resin composition which has excellent flowability when molded into a molded article, is less likely to produce burrs, and causes little mold staining. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described in detail.
[0011] [PAS Structure] The PAS in the present invention is a homopolymer or copolymer having a repeating unit of the formula -(Ar-S)- as the main structural unit. Here, "having as the main structural unit" means that the repeating unit is contained at 80 mol % or more. Ar includes units represented by the following formulas (A) to (K), among which formula (A) is particularly preferred.
[0012] [ka]
[0013] (R1 and R2 are substituents selected from hydrogen, alkyl groups, alkoxy groups, and halogen groups, and R1 and R2 may be the same or different.)
[0014] The repeating unit is the main constituent unit, and the copolymerization amount of the branching unit or crosslinking unit is preferably in the range of 0.10 mol % or more and 1.00 mol % or less per mole of -(Ar-S)- unit. From the viewpoint of obtaining a high molecular weight PAS, the lower limit of the copolymerization amount of the branching unit or crosslinking unit is preferably 0.10 mol % or more, more preferably 0.20 mol % or more, and even more preferably 0.30 mol % or more. On the other hand, from the viewpoint of preventing gelation of the polymer, the upper limit of the copolymerization amount of the branching unit or crosslinking unit is preferably 1.00 mol % or less, more preferably 0.80 mol % or less, and even more preferably 0.60 mol % or less.
[0015] [ka]
[0016] The PAS in the present invention may be any of a random copolymer, a block copolymer, and a mixture thereof, which contain the above repeating units.
[0017] Representative examples of these include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, their random copolymers, block copolymers, and mixtures thereof. Particularly preferred PASs include those having the following p-phenylene sulfide unit as the main structural unit of the polymer:
[0018] [ka]
[0019] and polyphenylene sulfide resins containing 80 mol % or more, particularly 90 mol % or more of the above.
[0020] [Characteristics of PAS resin] The PAS resin used in the PAS resin composition of the present invention is characterized by having a non-Newtonian index of 1.5 to 2.5, a carboxyl group content of 35 to 100 μmol / g, a cyclic content of 0.5 to 2.0% by weight, and a melt flow rate measured under conditions of 315.5°C and a load of 5,000 g of 5 to 300 g / 10 min.
[0021] The non-Newtonian index of the PAS resin is an index showing the shear rate dependency of the melt viscosity, and the lower limit is 1.5 or more, preferably 1.6 or more, more preferably 1.7 or more, and even more preferably 1.8 or more. Furthermore, the upper limit is 2.5 or less, preferably 2.3 or less, more preferably 2.2 or less, and even more preferably 2.0 or less. If the non-Newtonian index of the PAS resin used in the resin composition is less than 1.5, the resin is likely to flow into the gaps of the mold during injection molding, which is unsuitable because it increases the amount of flash. Furthermore, if the non-Newtonian index exceeds 2.5, the fluidity becomes insufficient, and the mold transferability during molding is poor. The non-Newtonian index (N) can be calculated using the following formula by measuring the shear rate and shear stress using a capillograph under conditions of 320°C and L / D10, which is the ratio of the orifice length (L) to the orifice diameter (D). SR=K / SSN (where N is the non-Newtonian exponent, SR is the shear rate (S -1 ), SS is shear stress (Pa), and K is a constant.) In general, the non-Newtonian index of a PAS increases as more branched structures are introduced, and for linear PAS it is usually 1.5 or less. There are various methods for introducing branched structures, but the index can be efficiently increased by introducing a polyhalogen compound with three or more halogen atoms.
[0022] The lower limit of the carboxyl group content of the PAS resin is 35 μmol / g, more preferably 45 μmol / g or more, and even more preferably 50 μmol / g or more. The upper limit is 100 μmol / g, more preferably 70 μmol / g or less. If the carboxyl group content is less than 35 μmol / g, the adhesion between the PAS resin and the filler and the reactivity with the alkoxysilane are not sufficiently obtained, which is inappropriate. On the other hand, if the carboxyl group content exceeds 100 μmol / g, the amount of volatile components during molding tends to increase, and voids are likely to occur in the molded product, which is not suitable. From the viewpoint of the amount of volatile components during molding and the tendency to reduce voids in the molded product, the carboxyl group content is preferably 70 μmol / g or less. The presence of a certain amount of carboxyl group content increases the adhesion with the filler and the reactivity with the coupling agent, improving the mechanical properties when made into a resin composition. The carboxyl group content of PAS here is measured by measuring an amorphous film of PAS resin with FT-IR (IR-810 infrared spectrophotometer manufactured by JASCO Corporation) and finding the 1,900 cm -1 The absorption at 1,730 cm originating from the carboxyl group -1 It can be estimated by comparing the absorption in the vicinity.
[0023] The upper limit of the amount of cyclic bodies in the PAS resin is 2.0% by weight, preferably 1.6% by weight or less, more preferably 1.4% by weight or less. The lower limit is 0.5% by weight. The PAS resin used in the present invention contains an oligomer component, which is roughly divided into a cyclic PAS component and a linear PAS component, and the main component is the cyclic PAS component. The cyclic body in the present invention refers to a cyclic PAS having 4 to 14 repeating units among the oligomer components, and the amount of the cyclic body refers to the total amount of the cyclic PAS having 4 to 14 repeating units. These cyclic body components are components that volatilize during injection molding, and cause mold staining by adhering and solidifying on the mold. The main component of the adhering components that cause mold staining is the cyclic body component, and if the amount of the cyclic body exceeds 2.0% by weight, it will cause the mold staining to worsen, burrs to occur, and the moldability will be deteriorated. Mold staining can be suppressed by suppressing the amount of the cyclic body in the PAS resin, and from the viewpoint of suppressing mold staining, the less the amount, the better. In addition, if the lower limit of the amount of cyclic substances in the resin is less than 0.5% by weight, the viscosity increases significantly and the melt fluidity decreases, so that the resin composition cannot enter the mold during injection molding and a molded product cannot be obtained, which is unsuitable. The cyclic substances referred to here are removed by washing the PAS resin with an organic polar solvent in the post-treatment process after the polymerization process in the production of the PAS resin, but if the PAS resin is not washed with an organic polar solvent after polymerization, the amount of cyclic substances generally exceeds 2.0% by weight. The amount of cyclic substances can be determined by dissolving the PAS resin in 1-chloronaphthalene at 250°C, cooling it, filtering the 1-chloronaphthalene insoluble components using a membrane filter with a pore size of 0.45 μm, and quantifying the amount of cyclic PAS of 4 to 14 monomers by high performance liquid chromatography (HPLC) measurement of the obtained soluble components.
[0024] The melt flow rate (hereinafter abbreviated as MFR) of the PAS resin has an upper limit of 300 g / 10 min, preferably 200 g / 10 min or less, more preferably 150 g / 10 min or less. The lower limit of the MFR is 5 g / 10 min, preferably 10 g / 10 min or more, more preferably 30 g / 10 min or more, and even more preferably 50 g / 10 min or more. If it exceeds 300 g / 10 min, the resin composition will have poor mechanical strength and toughness when molded, and if it is below 5 g / 10 min, it is inappropriate because the melt fluidity is low and the resin composition cannot enter the mold during injection molding, and a molded product cannot be obtained. The MFR can be evaluated according to ASTM D 1238-70, measured at a temperature of 315.5 ° C and a load of 5000 g.
[0025] The polydispersity (hereinafter abbreviated as Mw / Mn) of the PAS resin of the present invention, expressed by weight average molecular weight Mw / number average molecular weight Mn, is preferably 5.5 or more, more preferably 6.0 or more, even more preferably 6.5 or more, and even more preferably 7.0 or more. The larger the Mw / Mn, the higher the non-Newtonianity, and therefore the better the moldability during extrusion molding and blow molding. On the other hand, there is no particular upper limit for Mw / Mn, but it is usually 15.0 or less. In general, when the amount of branching / crosslinking agent is increased in the production of PAS resin, Mw / Mn increases, and when no branching / crosslinking agent is used, Mw / Mn is 5.0 or less. The Mw / Mn referred to here can be evaluated as a value measured using gel permeation chromatography (GPC) with 1-chloronaphthalene as an eluent at a column temperature of 210° C. and converted into a polystyrene standard.
[0026] In the present invention, from the viewpoint of obtaining a resin composition excellent in strength and toughness, the weight average molecular weight Mw of the PAS resin is preferably 60,000 or more, more preferably 75,000 or more, and even more preferably 90,000 or more. Also, from the viewpoint of obtaining a resin composition excellent in fluidity, the weight average molecular weight is preferably 150,000 or less, more preferably 130,000 or less, and even more preferably 120,000 or less.
[0027] The cooling crystallization temperature (Tmc) of PAS resin measured at a cooling rate of 20°C / min is preferably 190°C or higher, more preferably 200°C or higher, even more preferably 210°C or higher, and even more preferably 220°C or higher, from the viewpoint of the crystallization rate that affects the molding cycle time. Also, from the viewpoint of the solidification rate during molding and the crystallinity of the molded product, it is preferably 230°C or lower. In general, the cooling crystallization temperature tends to decrease as the branched and crosslinked structures increase, so the Tmc tends to decrease as the amount of polyhalogenated aromatic compounds having three or more halogens in the raw material increases. In the manufacturing process of PAS resin, the cooling crystallization temperature is improved by acid treatment in the post-treatment process. The reason for this is unclear, but it is assumed that the cooling crystallization temperature is decreased due to the influence of the metal species at the polymer end.
[0028] The method for producing the PAS resin of the present invention will be specifically described below.
[0029] First, the raw materials used in the production of PAS resin will be described.
[0030] [Sulfidizing agent] The sulfidizing agent used in the present invention may be any agent capable of introducing a sulfide bond into a halogenated aromatic compound, and examples thereof include alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide.
[0031] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these. Among these, lithium sulfide and / or sodium sulfide are preferred, and sodium sulfide is more preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or in the form of anhydrides. The aqueous mixture refers to an aqueous solution, or a mixture of an aqueous solution and a solid component, or a mixture of water and a solid component. Generally available, inexpensive alkali metal sulfides are hydrates or aqueous mixtures, so it is preferable to use alkali metal sulfides in such forms.
[0032] Specific examples of alkali metal hydrosulfides include lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these. Among these, lithium hydrosulfide and / or sodium hydrosulfide are preferred, and sodium hydrosulfide is more preferably used.
[0033] In addition, an alkali metal sulfide prepared in a reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide can also be used. In addition, an alkali metal sulfide prepared in advance by contacting an alkali metal hydrosulfide with an alkali metal hydroxide can also be used. These alkali metal hydrosulfides and alkali metal hydroxides can be used as hydrates or aqueous mixtures, or in the form of anhydrides, with the hydrates or aqueous mixtures being preferred from the viewpoints of availability and cost.
[0034] Furthermore, an alkali metal sulfide prepared in the reaction system from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide can also be used.Alkali metal sulfides prepared in advance by contacting an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide with hydrogen sulfide can also be used.Hydrogen sulfide may be used in any form, be it a gas, liquid, or aqueous solution.
[0035] [Dihalogenated aromatic compound] When producing the PAS resin of the present invention, a dihalogenated aromatic compound is used. Examples of the dihalogenated aromatic compound used include dihalogenated benzenes such as p-dichlorobenzene, o-dichlorobenzene, m-dichlorobenzene, p-dibromobenzene, o-dibromobenzene, m-dibromobenzene, 1-bromo-4-chlorobenzene, and 1-bromo-3-chlorobenzene, and dihalogenated aromatic compounds containing substituents other than halogen such as 1-methoxy-2,5-dichlorobenzene, 1-methyl-2,5-dichlorobenzene, 1,4-dimethyl-2,5-dichlorobenzene, 1,3-dimethyl-2,5-dichlorobenzene, 2,5-dichlorobenzoic acid, 3,5-dichlorobenzoic acid, 2,5-dichloroaniline, and 3,5-dichloroaniline. Among them, dihalogenated aromatic compounds mainly composed of p-dihalogenated benzenes such as p-dichlorobenzene are preferred. From the viewpoint of preventing depolymerization of the PAS resin during polymerization, the lower limit of the amount of the dihalogenated aromatic compound is preferably 0.99 mol or more per 1.00 mol of the sulfidizing agent, more preferably 1.00 mol or more. From the viewpoint of obtaining a high molecular weight PAS resin, the upper limit of the amount of the dihalogenated aromatic compound is preferably 1.03 mol or less per 1.00 mol of the sulfidizing agent, more preferably 1.02 mol or less. The dihalogenated aromatic compound may be used alone or as a mixture of two or more different types.
[0036] [Branching / Crosslinking Agents] When producing the PAS resin of the present invention, it is preferable to use a branching / crosslinking agent.Specific examples include polyhalogenated aromatic compounds having three or more halogens, such as 1,3,5-trichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2,4,5-tetrachlorobenzene, hexachlorobenzene, and 1,4,6-trichloronaphthalene, and polyhalogenated aromatic compounds having three or more halogens and containing substituents other than halogens, such as 2,3,6-trichlorobenzoic acid, 2,4,5-trichlorobenzoic acid, 2,4,6-trichlorobenzoic acid, 2,3,4-trichloroaniline, and 2,4,6-trichloroaniline.Among them, trihalogenated aromatic compounds represented by 1,3,5-trichlorobenzene and 1,2,4-trichlorobenzene are preferable in view of increasing the crystallization temperature of the resulting PAS resin when cooled. When a trihalogenated aromatic compound is used as a branching / crosslinking agent, from the viewpoint of increasing the molecular weight of the PAS resin, the amount of the trihalogenated aromatic compound is preferably 0.10 mol% or more relative to 1.00 mol of the sulfidizing agent, more preferably 0.20 mol% or more, and even more preferably 0.30 mol% or more. On the other hand, from the viewpoint of preventing the gelation of the polymer due to an increase in branching / crosslinking, the amount of the trihalogenated aromatic compound is preferably 1.00 mol% or less relative to 1.00 mol of the sulfidizing agent, more preferably 0.80 mol% or less, even more preferably 0.60 mol% or less, and even more preferably 0.50 mol% or less. In order to increase toughness, the amount of the trihalogenated compound is preferably even less, more preferably 0.40 mol% or less, and even more preferably 0.30 mol% or less. The branching / crosslinking agent may be used alone or in a mixture of two or more different types. The carboxyl group content increases by using a polyhalogenated aromatic compound as a branching / crosslinking agent. The reason for this is unclear, but it is presumed to be due to the high reactivity of polyhalogenated aromatic compounds. In addition, in general, the carboxyl group content when no polyhalogenated aromatic compounds are used is lower than when a trihalogenated aromatic compound is used.The carboxyl group content of the PAS resin referred to here is determined by measuring an amorphous film of the PAS resin with FT-IR (IR-810 infrared spectrophotometer manufactured by JASCO Corporation) and finding the 1,900 cm wavelength derived from the benzene ring. -1 The absorption at 1,730 cm originating from the carboxyl group -1 It can be estimated by comparing the absorption in the vicinity.
[0037] [Organic polar solvents] In the present invention, an organic polar solvent is used as the polymerization solvent. As the organic polar solvent to be used, an organic amide solvent can be preferably exemplified. Specific examples include N-alkylpyrrolidones such as N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and N-cyclohexyl-2-pyrrolidone, caprolactams such as N-methyl-ε-caprolactam, aprotic organic solvents such as 1,3-dimethyl-2-imidazolidinone, N,N-dimethylacetamide, N,N-dimethylformamide, and hexamethylphosphoric triamide, and mixtures thereof, which are preferably used because of their high reaction stability. Among these, N-methyl-2-pyrrolidone and 1,3-dimethyl-2-imidazolidinone are preferred, and N-methyl-2-pyrrolidone is more preferred.
[0038] The amount of the organic polar solvent used is selected from the range of 2.00 to 10.00 moles, preferably 2.25 to 6.00 moles, more preferably 2.50 to 5.50 moles, per 1.00 mole of the sulfidizing agent.
[0039] [Polymerization aid] In order to obtain a relatively high molecular weight PAS in a short time, it is also a preferred embodiment to use a polymerization aid. Here, the polymerization aid means a substance that has the effect of increasing the viscosity of the obtained PAS. Specific examples of such polymerization aids include organic carboxylates, water, alkali metal chlorides, organic sulfonates, alkali metal sulfates, alkaline earth metal oxides, alkali metal phosphates, and alkaline earth metal phosphates. These can be used alone or in combination of two or more. Among them, organic carboxylates, water, and alkali metal chlorides are preferred, and alkali metal carboxylates are preferred as organic carboxylates, and lithium chloride is preferred as alkali metal chlorides.
[0040] The above alkali metal carboxylate has the general formula R(COOM) n (wherein R is an alkyl group, a cycloalkyl group, an aryl group, an alkylaryl group, or an arylalkyl group having 1 to 20 carbon atoms; M is an alkali metal selected from lithium, sodium, potassium, rubidium, and cesium; and n is an integer of 1 to 3). The alkali metal carboxylate can also be used as a hydrate, anhydride, or an aqueous solution. Specific examples of the alkali metal carboxylate include lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, sodium benzoate, sodium phenylacetate, potassium p-toluate, and mixtures thereof.
[0041] The alkali metal carboxylate may be synthesized by adding and reacting an organic acid with one or more compounds selected from the group consisting of alkali metal hydroxides, alkali metal carbonates, and alkali metal bicarbonates in approximately equal chemical equivalents. Among the above alkali metal carboxylates, lithium salts are highly soluble in the reaction system and have a large auxiliary effect, but are expensive. On the other hand, potassium, rubidium, and cesium salts are thought to have insufficient solubility in the reaction system, so sodium acetate, which is inexpensive and has moderate solubility in the polymerization system, is most preferably used.
[0042] The water used in the above polymerization aid is preferably distilled water or ion-exchanged water so as not to impair the desired effect of chemical modification of the PAS.
[0043] In the present invention, it is preferable to use an alkali metal carboxylate as the polymerization aid, and more preferably to use sodium acetate. As the lower limit of the polymerization aid, it is preferable to have 0.06 mol or more of the polymerization aid present per 1.00 mol of the sulfidizing agent. From the viewpoint of higher molecular weight, it is more preferable to have 0.10 mol or more, and even more preferable to have 0.15 mol or more. As the upper limit of the polymerization aid, it is preferable to have 0.29 mol or less, more preferably 0.27 mol or less, and even more preferably 0.25 mol or less, per 1.00 mol of the sulfidizing agent. If it exceeds the above preferred range, the PAS particles become coarse and the transportability decreases, which is not preferable.
[0044] In addition, when water is used as a polymerization aid, it is preferable to have 0.50 moles or more of water present in the reaction vessel relative to 1.00 moles of the sulfidizing agent. In terms of obtaining a higher molecular weight, it is more preferable to have 0.60 moles or more, and even more preferable to have 0.70 moles or more. As the upper limit when water is used as a polymerization aid, it is preferable to have 1.50 moles or less of water present relative to 1.00 moles of the sulfidizing agent, more preferably 1.25 moles or less, and even more preferably 1.00 moles or less, from the viewpoint of safety related to the pressure in the reaction vessel and the viewpoint of handling related to the particle size of the obtained polymer.
[0045] Of course, two or more of these polymerization aids can be used in combination. For example, when an alkali metal carboxylate and water are used in combination, a higher molecular weight can be achieved with smaller amounts of the alkali metal carboxylate and water.
[0046] There is no particular designation for the timing of addition of these polymerization aids, and they may be added at any time during the pre-step, at the start of polymerization, or during the polymerization reaction step, as described below, or may be added in multiple batches. When an alkali metal carboxylate is used as the polymerization aid, it is more preferable to add it at the start of the pre-step or at the start of polymerization simultaneously with other additives, since this is easier to add. When water is used as the polymerization aid, it is effective to add it during the polymerization reaction step after the dihalogenated aromatic compound and the branching / crosslinking agent have been added.
[0047] [Polymerization stabilizer] A polymerization stabilizer can be used to stabilize the polymerization reaction system and prevent side reactions. The polymerization stabilizer contributes to the stabilization of the polymerization reaction system and suppresses undesirable side reactions. One indicator of side reactions is the generation of thiophenol. The addition of a polymerization stabilizer can suppress the generation of thiophenol. Specific examples of polymerization stabilizers include compounds such as alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, and alkaline earth metal carbonates. Among these, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred. The above-mentioned alkali metal carboxylates also act as polymerization stabilizers, and therefore are included as one of the polymerization stabilizers. In addition, as mentioned above, when an alkali metal hydrosulfide is used as a sulfidizing agent, it is particularly preferable to use an alkali metal hydroxide at the same time, but here, an alkali metal hydroxide that is in excess of the sulfidizing agent can also be a polymerization stabilizer.
[0048] These polymerization stabilizers can be used alone or in combination of two or more. The polymerization stabilizer is preferably used in a ratio of usually 0.02 mol to 0.20 mol, preferably 0.03 mol to 0.10 mol, more preferably 0.04 mol to 0.09 mol, per 1.00 mol of the charged sulfidizing agent. If this ratio is small, the stabilizing effect is insufficient, and conversely, if it is too large, it is economically disadvantageous and the polymer yield tends to decrease.
[0049] The timing of adding the polymerization stabilizer is not particularly specified, and it may be added at any time during the pre-step, at the start of polymerization, or during the polymerization reaction step described below, or may be added in multiple portions. However, it is more preferable to add it simultaneously at the start of the pre-step or at the start of polymerization, as this is easier.
[0050] Next, a preferred method for producing the PAS of the present invention will be specifically described in order, including a pre-process, a polymerization reaction process, a recovery process, and a post-treatment process, although the present invention is not limited to this method.
[0051] [Pre-process] When producing the PAS of the present invention, the sulfidizing agent is used in the form of a hydrate. It is preferable to heat the mixture containing the organic polar solvent and the sulfidizing agent and remove excess water from the system before adding the dihalogenated aromatic compound and the branching / crosslinking agent.
[0052] As described above, the sulfidizing agent may be prepared in situ in the reaction system from an alkali metal hydrosulfide and an alkali metal hydroxide, or in a tank separate from the polymerization tank. There is no particular restriction on this method, but a preferable method is to add an alkali metal hydrosulfide and an alkali metal hydroxide to an organic polar solvent in an inert gas atmosphere at room temperature to 150°C, preferably from room temperature to 100°C, and then heat the mixture to at least 150°C or higher, preferably 180°C to 260°C, under normal pressure or reduced pressure, to distill off water. A polymerization aid may be added at this stage. The order of charging these raw materials may be random, or they may be charged simultaneously. Toluene or the like may be added to promote the distillation of water, and the reaction may be carried out.
[0053] At the end of the previous step, i.e., before the polymerization reaction step, the amount of water in the system is preferably 0.01 mol to 1.00 mol per 1.00 mol of the charged sulfidizing agent. Here, the amount of water in the system is the amount of water charged into the polymerization system minus the amount of water removed from the polymerization system. The charged water may be in any form, such as water, an aqueous solution, or water of crystallization.
[0054] [Polymerization process] When producing the PAS of the present invention, it is preferable to carry out a polymerization step in which the reactant prepared in the previous step is brought into contact with a dihalogenated aromatic compound and a branching / crosslinking agent in an organic polar solvent to cause a polymerization reaction.
[0055] In the polymerization step, it is preferable to have 0.06 mol or more and 0.29 mol or less of an alkali metal carboxylate present relative to 1.00 mol of a sulfidizing agent, and to have 0.99 mol or more and 1.03 mol or less of a dihalogenated aromatic compound and 0.10 mol % or more and 1.00 mol % or less of a trihalogenated aromatic compound present relative to 1.00 mol of the sulfidizing agent (Step 1).
[0056] Here, the alkali metal carboxylate plays a role as a polymerization aid as described above, and it is preferable to have the alkali metal carboxylate present in an amount of 0.06 mol or more, since the molecular weight of the resulting PAS is high. More preferably, it is 0.10 mol or more, and even more preferably, it is 0.15 mol or more. The alkali metal carboxylate is preferably present in an amount of 0.29 mol or less, more preferably 0.27 mol or less, and even more preferably 0.25 mol or less. If it exceeds the above preferred range, the PAS particles become coarse and the transportability decreases, which is not preferable. Also, as described above, the alkali metal carboxylate may be added in a previous process.
[0057] In the polymerization step, the trihalogenated aromatic compound is preferably present in an amount of 0.10 mol % or more and 1.00 mol % or less per 1.00 mol of the sulfidizing agent.
[0058] Here, the trihalogenated aromatic compound plays a role as a branching / crosslinking agent as described above. From the viewpoint of increasing the molecular weight of PAS, the amount of the trihalogenated aromatic compound is preferably 0.10 mol % or more relative to 1.00 mol of the sulfidizing agent, more preferably 0.20 mol % or more, and even more preferably 0.30 mol % or more. On the other hand, from the viewpoint of preventing the gelation of the polymer due to an increase in branching / crosslinking, the amount of the trihalogenated aromatic compound is preferably 1.00 mol % or less relative to 1.00 mol of the sulfidizing agent, more preferably 0.80 mol % or less, even more preferably 0.60 mol % or less, and even more preferably 0.50 mol % or less.
[0059] When starting the polymerization process, an organic polar solvent, a sulfidizing agent, a dihalogenated aromatic compound, and a branching / crosslinking agent are mixed, desirably in an inert gas atmosphere, at a temperature range of 25°C to 240°C, preferably 100°C to 230°C. A polymerization aid may be added at this stage. The order of charging these raw materials may be random, or they may be charged simultaneously.
[0060] The mixture is usually heated to a temperature range of 200° C. to 280° C. There is no particular restriction on the heating rate, but a rate of 0.01° C. / min to 5° C. / min is usually selected, and a range of 0.1° C. / min to 3° C. / min is more preferable. As long as it is within the above-mentioned heating rate range, it does not necessarily have to be a constant rate, and there may be a constant temperature section, or the temperature may be raised in multiple stages without any problems, and there may be a section where the heating rate becomes temporarily negative as long as it does not impair the essence of the present invention.
[0061] In general, the temperature is finally raised to 250° C. to 280° C., and the reaction is carried out at that temperature for usually 0.25 hours to 50 hours, preferably 0.5 hours to 20 hours.
[0062] Before reaching the final temperature, for example, a method of reacting at 200°C to 250°C for a certain time and then raising the temperature to 250°C to 280°C or less is effective in obtaining a higher molecular weight. In this case, the reaction time at 200°C to 250°C is usually selected in the range of 0.25 hours to 20 hours, preferably 0.25 hours to 10 hours. In addition, it is desirable to carry out the reaction so that the conversion rate of the halogenated aromatic compound in the system at the time of raising the temperature to the range of 250°C to 280°C or less after reacting at 200°C to 250°C for a certain time is 60% or more, preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. The conversion rate of the halogenated aromatic compound (abbreviated as HA here) is a value calculated by the following formula. The amount of HA remaining can usually be determined by gas chromatography. (A) When a halogenated aromatic compound is added in excess of the alkali metal sulfide in terms of molar ratio Conversion rate = [HA charge amount (mol) - HA remaining amount (mol)] / [HA charge amount (mol) - HA excess amount (mol)] (B) Cases other than (A) above Conversion rate = [HA charge amount (mol) - HA remaining amount (mol)] / [HA charge amount (mol)]
[0063] In the present invention, the polymerization time in the polymerization step is usually preferably 60 minutes or more, more preferably 120 minutes or more, from the viewpoint of increasing the molecular weight of the PAS. On the other hand, the upper limit of the polymerization time is preferably 240 minutes or less, more preferably 210 minutes or less, and even more preferably 180 minutes or less, from the viewpoint of productivity. The polymerization time here refers to the time including the temperature increase and decrease time within the temperature range of 200°C to 280°C from the time when the sulfidizing agent and the halogenated aromatic compound are charged until the polymerization reaction product is discharged from the reaction vessel.
[0064] In the polymerization step, it is preferable that water is present in the reaction vessel at 0.50 moles or more per 1.00 moles of the sulfidizing agent. In terms of obtaining a higher molecular weight, 0.60 moles or more is more preferable, and 0.70 moles or more is even more preferable. When water is used as a polymerization aid, the upper limit is preferably 1.50 moles or less per 1.00 moles of the sulfidizing agent, more preferably 1.25 moles or less, and even more preferably 1.00 moles or less, from the viewpoint of safety related to the pressure in the reaction vessel and the viewpoint of handling related to the particle size of the obtained polymer. The water content in the polymerization step represents the water content in the temperature range of 250°C to 280°C in the polymerization step, and is the amount obtained by subtracting the amount of water removed from the polymerization system from the amount of water charged into the polymerization system and the amount of water generated by the polymerization reaction.
[0065] As a method for making water present in the reaction vessel in an amount of 0.50 mol to 1.50 mol per 1.00 mol of the sulfidizing agent, water may be added to the reaction vessel, or the reaction vessel may be partially opened to remove water. Also, a combination of these methods is possible. From the viewpoints of safety and simplicity, it is preferable to add water.
[0066] [Recovery process] When producing the PAS of the present invention, after the polymerization is completed, solid matter is recovered from the polymerization reaction product containing the polymer, the solvent, etc. The solid matter referred to here includes not only the PAS but also water-soluble substances such as by-product salts and unreacted sulfidizing agents. Any known method may be used for the recovery method.
[0067] For example, after the polymerization reaction is completed, the polymer particles may be collected by gradually cooling. The cooling speed is not particularly limited, but is usually about 0.1°C / min to 3°C / min. It is not necessary to cool at the same speed throughout the entire cooling process, and a method of gradually cooling at a speed of 0.1°C / min to 1°C / min until the polymer particles crystallize and precipitate, and then at a speed of 1°C / min or more may be used.
[0068] Another preferred method is to carry out the above recovery under rapid cooling conditions. A preferred recovery method is the flash method. In the flash method, the polymerization reaction product is subjected to high temperature and high pressure (usually 250°C or higher, 8 kg / cm 2 This is a method in which the polymer is flashed from the above state into an atmosphere of normal pressure, reduced pressure, or pressurized pressure, and the solvent is distilled off while the polymer is powdered and recovered. Flashing here means that the polymerization reaction product is ejected from a nozzle. Specific examples of the atmosphere for flashing include nitrogen or water vapor at normal pressure, and the temperature is usually selected in the range of 150°C to 250°C.
[0069] In the production of the PAS of the present invention, either a method of recovering particulate PAS by slow cooling or a method of recovering powdered PAS by rapid cooling may be used, but in the method of recovering particulate PAS by slow cooling, fine particles are formed and are easily separated and removed in the liquid side during solid-liquid separation, so the functional group content of the obtained PAS is likely to be low, and slow cooling takes a long time. Therefore, the method of flashing the polymerization reaction product from a high-temperature and high-pressure state into an atmosphere of normal pressure, reduced pressure, or pressurized pressure, distilling off the solvent, and simultaneously rapid cooling to recover powdered PAS is preferred (Step 2).
[0070] [Post-processing process] The PAS may be produced through the above-mentioned polymerization and recovery steps, and then subjected to hot water treatment, acid treatment, washing with an organic solvent, or treatment with an alkali metal or alkaline earth metal.
[0071] In the present invention, since the solid obtained through the above recovery process contains not only PAS but also water-soluble substances such as by-product salts and unreacted sulfidizing agents, hot water washing is preferable. The hot water treatment is performed as follows. When hot water treatment of PAS, it is preferable to set the temperature of hot water to 100°C or higher, more preferably 120°C or higher, even more preferably 150°C or higher, and particularly preferably 170°C or higher. Temperatures below 100°C are not preferable because the effect of the preferable chemical modification of PAS is small. In order to express the effect of the preferable chemical modification of PAS by hot water washing, it is preferable that the water used is distilled water or ion-exchanged water. There is no particular restriction on the operation of the hot water treatment. It is performed by a method in which a predetermined amount of PAS is added to a predetermined amount of water, and heated and stirred in a pressure vessel, or a method in which hot water treatment is performed continuously. The ratio of PAS to water is preferably higher, but usually a bath ratio of 200g or less of PAS per 1 liter of water (weight of cleaning solution relative to the weight of dry PAS) is selected.
[0072] In the present invention, from the viewpoint of obtaining a PAS having a high functional group content and a high crystallization temperature under cooling, it is preferable to treat the PAS with an acid. The acid treatment is carried out as follows. There are no particular limitations on the acid used in the acid treatment of the PAS, so long as it does not have the effect of decomposing the PAS, and examples of the acid include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid, and propylic acid. Among these, acetic acid and hydrochloric acid are more preferably used. On the other hand, acids that decompose and deteriorate the PAS, such as nitric acid, are not preferable.
[0073] In order to avoid undesirable decomposition of the reactive functional groups at the terminals, it is preferable to carry out the treatment in an inert atmosphere. Furthermore, in order to remove any remaining components, it is preferable to wash the PAS several times with warm water after the acid treatment.
[0074] The acid treatment may be performed, for example, by immersing the PAS in an acid or an aqueous solution of an acid, and stirring or heating may be performed if necessary. For example, when acetic acid is used, a sufficient effect can be obtained by immersing the PAS in an aqueous solution of acetic acid with a pH of 3 or more but less than 7 heated to 80°C to 200°C and stirring for 30 minutes. The pH after the treatment may be higher than the pH of the aqueous solution of acetic acid used, for example, about pH 4 to 8. In order to remove residual acid or salt from the acid-treated PAS, it is preferable to wash the PAS several times with water or hot water. The water used for washing is preferably distilled water or ion-exchanged water so as not to impair the effect of the preferable chemical modification of the PAS by the acid treatment. The acid-treated PAS is preferable because it has excellent reactivity during molding and has a high crystallization temperature when cooled.
[0075] When drying PAS after acid treatment, if the drying temperature is too high, the PAS particles will fuse together and the specific surface area will become smaller, and there is a tendency that sufficient cleaning effect cannot be achieved in the organic solvent washing described later. Therefore, the upper limit is preferably 170°C or less, more preferably 150°C or less. In addition, from the viewpoint of drying efficiency, the lower limit of the drying temperature is preferably 70°C or more, more preferably 100°C or more, and even more preferably 120°C or more. When the drying temperature of PAS is in the above preferred range, the specific surface area of the PAS after drying becomes large, and there is a tendency that oligomers in the PAS are easily washed and removed sufficiently in the organic solvent washing described later. There is also a tendency that drying can be performed efficiently in a short time. In addition, it is preferable that the atmosphere during drying is a non-oxidizing condition, and an inert gas atmosphere such as nitrogen, helium, and argon is preferable, and in particular, from the viewpoint of economy and ease of handling, a nitrogen atmosphere is more preferable. By drying PAS in such an atmosphere, there is a tendency that denaturation due to oxidation of PAS can be prevented.
[0076] In addition, the drying time is not particularly limited, but the lower limit is, for example, 0.5 hours or more, and preferably 1 hour or more. The upper limit is preferably 50 hours or less, more preferably 20 hours or less, and even more preferably 10 hours or less. When the drying time of the PAS is within the above-mentioned preferred range, the PAS can be produced industrially and efficiently.
[0077] Here, there is no particular limitation on the dryer used for drying, and a general vacuum dryer or hot air dryer can be used, and it is also possible to use a rotary type or a heating device with stirring blades, a fluidized bed dryer, etc. From the viewpoint of efficiently and uniformly drying the PAS, it is preferable to dry using a rotary type or a heating device with stirring blades.
[0078] In the present invention, in order to set the amount of cyclic bodies in the obtained PAS within a preferred range, it is preferable to wash the PAS with an organic solvent. There is no restriction on the order of washing with an organic solvent and the above-mentioned hot water washing or acid washing, but carrying out washing after acid washing improves the efficiency of removing cyclic body and oligomer components. Washing with an organic solvent is as follows. There is no particular restriction on the organic solvent used for washing the PAS, so long as it does not have the action of decomposing the PAS. Examples of organic solvents that can be used to clean PAS include nitrogen-containing polar solvents such as N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, 1,3-dimethylimidazolidinone, hexamethylphosphoramide, and piperazinones; sulfoxide and sulfone solvents such as dimethyl sulfoxide, dimethyl sulfone, and sulfolane; ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, and acetophenone; ether solvents such as dimethyl ether, dipropyl ether, dioxane, and tetrahydrofuran; halogen-based solvents such as chloroform, methylene chloride, trichloroethylene, ethylene dichloride, perchloroethylene, monochloroethane, dichloroethane, tetrachloroethane, perchloroethane, and chlorobenzene; alcohol and phenol solvents such as methanol, ethanol, propanol, butanol, pentanol, ethylene glycol, propylene glycol, phenol, cresol, polyethylene glycol, and polypropylene glycol; and aromatic hydrocarbon solvents such as benzene, toluene, and xylene. Among these organic solvents, it is particularly preferable to use N-methyl-2-pyrrolidone, acetone, dimethylformamide, chloroform, etc. Furthermore, these organic solvents are used alone or in combination of two or more kinds.
[0079] As a method for washing with an organic solvent, for example, there is a method of immersing PAS in an organic solvent, and it is also possible to stir or heat it appropriately if necessary. There is no particular limit to the washing temperature when washing PAS with an organic solvent, and any temperature from room temperature to about 300°C can be selected. The higher the washing temperature, the higher the washing efficiency tends to be, but usually a washing temperature of room temperature to 150°C can be sufficiently effective. It is also possible to wash under pressure in a pressure vessel at a temperature above the boiling point of the organic solvent. There is also no particular limit to the washing time. Although it depends on the washing conditions, in the case of batch washing, a sufficient effect is usually obtained by washing for 5 minutes or more. It is also possible to wash in a continuous manner. The post-treatment step is preferably performed by performing any one of acid treatment, hot water treatment, and washing with an organic solvent, and it is preferable to use two or more types of treatments in combination from the viewpoint of removing impurities.
[0080] The water content of the PAS before washing with an organic solvent is preferably 30% by weight or less. Since water is a poor solvent for impurities such as cyclic and oligomer components in the PAS, reducing the water content of the PAS tends to reduce the impurities when washing the PAS with an organic solvent. When the organic solvent used to wash the PAS is a non-water-soluble organic solvent such as chloroform or toluene, a stable washing effect tends to be obtained regardless of the water content of the PAS, so it is not necessary to reduce the water content of the PAS to 30% by weight or less. However, considering that N-methyl-2-pyrrolidone, which is particularly preferably used from the viewpoint of availability, is a water-soluble organic solvent, it is a more preferable method to reduce the water content in the PAS. Here, the lower limit of the water content of the PAS before washing with an organic solvent is preferably as low as possible in order to enhance the washing effect, and 0% by weight, which means that no water is contained in the PAS at all, is most preferable. On the other hand, the upper limit is more preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 1% by weight or less. When the water content of the PAS before washing with an organic solvent is within the above-mentioned preferred range, the amount of impurities in the PAS tends to be reduced more easily when a water-soluble organic solvent is used for washing the PAS. As a method for reducing the water content to 30% by weight or less, as mentioned above, the method of drying the PAS after the acid treatment can be mentioned.
[0081] Here, the water content of the PAS in the present invention is measured according to the Karl Fischer method in accordance with Japanese Industrial Standard JIS K 7251.
[0082] Examples of the method of treating with an alkali metal or alkaline earth metal include a method of adding an alkali metal salt or an alkaline earth metal salt before, during, or after the previous step, a method of adding an alkali metal salt or an alkaline earth metal salt into a polymerization vessel before, during, or after the polymerization step, or a method of adding an alkali metal salt or an alkaline earth metal salt at the beginning, middle, or end of the washing step. The easiest method among them is a method of adding an alkali metal salt or an alkaline earth metal salt after removing residual oligomers and residual salts by washing with an organic solvent or washing with warm or hot water. The alkali metal or alkaline earth metal is preferably introduced into the PAS in the form of an alkali metal ion or an alkaline earth metal ion such as an acetate, hydroxide, or carbonate. It is also preferable to remove excess alkali metal salt or alkaline earth metal salt by washing with warm water or the like. The concentration of the alkali metal ion or alkaline earth metal ion when introducing the alkali metal or alkaline earth metal is preferably 0.001 mmol or more per 1 g of PAS, more preferably 0.01 mmol or more. The temperature is preferably 50° C. or higher, more preferably 75° C. or higher, and particularly preferably 90° C. or higher. There is no particular upper limit to the temperature, but from the viewpoint of operability, it is usually preferable that the temperature is 280° C. or lower. The bath ratio (weight of cleaning solution to weight of dry PAS) is preferably 0.5 or higher, more preferably 3 or higher, and even more preferably 5 or higher.
[0083] In the present invention, it is preferable to carry out, as post-treatment steps, a step (step 3) of washing a solid material containing polyarylene sulfide with water and then treating it with an acid, and a step (step 4) of washing the polyarylene sulfide with an organic solvent following step 3. This allows the oligomer components to be efficiently removed.
[0084] [Heat treatment process] In addition, the PAS of the present invention can be used after being subjected to a heat treatment in which, after the completion of polymerization, it is heated in an oxygen atmosphere or heated with the addition of a crosslinking agent such as a peroxide to increase the molecular weight.
[0085] When dry heat treatment is performed for the purpose of increasing the molecular weight by thermal oxidation crosslinking, the temperature is preferably 160°C to 260°C, more preferably 170°C to 250°C. The oxygen concentration is desirably 5% by volume or more, more desirably 8% by volume or more. There is no particular upper limit to the oxygen concentration, but the limit is about 50% by volume. The treatment time is preferably 0.5 hours to 100 hours, more preferably 1 hour to 50 hours, and even more preferably 2 hours to 25 hours. The heat treatment device may be a normal hot air dryer or a rotary type or a heating device with a stirring blade. For efficient and more uniform treatment, it is preferable to use a rotary type or a heating device with a stirring blade.
[0086] Dry heat treatment can also be performed for the purpose of increasing viscosity while suppressing excessive thermal oxidation crosslinking and removing volatiles. The temperature is preferably 130°C to 250°C, more preferably 160°C to 250°C. In this case, the oxygen concentration is preferably less than 5% by volume, and more preferably 2% by volume or less. The lower limit of the treatment time can be 0.1 hours or more, and from the viewpoint of stabilizing the conditions in the heat treatment device and the associated stable control of the high molecular weight by heat treatment, it is preferably 0.25 hours or more, more preferably 0.5 hours or more, and even more preferably 1 hour or more. The upper limit of the treatment time can be 50 hours or less, and from the viewpoint of productivity, it is preferably 20 hours or less, and more preferably 10 hours or less. The heat treatment device may be a normal hot air dryer or a heating device with a rotating or stirring blade. In order to perform efficient and more uniform treatment, it is more preferable to use a heating device with a rotating or stirring blade.
[0087] [Characteristics of PAS resin composition] The PAS resin composition obtained in the present invention is a PAS resin composition obtained by blending a PAS resin, a filler, and an alkoxysilane having at least one functional group. The filler referred to here is a fibrous filler such as glass fiber, carbon fiber, carbon nanotube, carbon nanohorn, potassium titanate whisker, zinc oxide whisker, calcium carbonate whisker, wollastonite whisker, aluminum borate whisker, aramid fiber, alumina fiber, silicon carbide fiber, ceramic fiber, asbestos fiber, gypsum fiber, metal fiber, or a silicate such as fullerene, talc, wollastonite, zeolite, sericite, mica, kaolin, clay, pyrophyllite, silica, bentonite, asbestos, alumina silicate, or a silicon oxide. Examples of fillers that can be used include metal compounds such as magnesium oxide, alumina, zirconium oxide, titanium oxide, and iron oxide; carbonates such as calcium carbonate, magnesium carbonate, and dolomite; sulfates such as calcium sulfate and barium sulfate; hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide; glass beads, glass flakes, glass powder, ceramic beads, boron nitride, silicon carbide, carbon black, and non-fibrous fillers such as silica and graphite. Of these, fibrous fillers such as glass fiber, carbon fiber, ceramic fiber, and aramid fiber are preferred, and glass fiber is more preferred.
[0088] The lower limit of the amount of the filler must be 1 part by weight or more relative to 100 parts by weight of the PAS resin, and from the viewpoint of tensile strength and dimensional accuracy when molded, 30 parts by weight or more is preferable, and 60 parts by weight or more is more preferable. From the viewpoint of obtaining a PAS resin composition with excellent fluidity, the upper limit must be 200 parts by weight or less relative to 100 parts by weight of the PAS resin, and 100 parts by weight or less is preferable, and 70 parts by weight or less is more preferable. If the amount of the filler is less than 1 part by weight relative to 100 parts by weight of the PAS resin, the tensile strength and dimensional accuracy when molded may be significantly reduced, which is not preferable, and if the amount of the filler is more than 200 parts by weight relative to 100 parts by weight of the PAS resin, the fluidity of the obtained PAS resin composition is significantly reduced, which is not preferable. In this case, a sizing agent may be applied to the filler to improve processability. In addition, the amount of the sizing agent applied to a general filler is 1.0% by weight or less relative to the weight of the filler.
[0089] In the present invention, it is essential that the PAS resin composition contains an alkoxysilane having at least one functional group.
[0090] The alkoxysilane referred to here is preferably a silane coupling agent.Specific examples include N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, N-phenylaminomethyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropylmethyldimethoxysilane, 3-isocyanatepropylmethyldiethoxysilane, 3-isocyanatepropylethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc. Among them, an alkoxysilane having at least one functional group selected from an epoxy group, an isocyanate group, and an amino group is more preferable, and from the viewpoint of strength, an alkoxysilane having an isocyanate group is preferable, and from the viewpoint of preventing sink marks and uneven transfer, an alkoxysilane having an epoxy group is preferable. From the viewpoint of strength when the obtained PAS resin composition is molded into a molded product, the lower limit of the amount of alkoxysilane to be blended must be 0.1 parts by weight or more relative to 100 parts by weight of PAS resin, more preferably 0.2 parts by weight or more, and more preferably 0.3 parts by weight or more. From the viewpoint of fluidity when molded into a molded product, the upper limit must be 10 parts by weight or less relative to 100 parts by weight of PAS resin, preferably 5 parts by weight or less, and more preferably 1 part by weight or less. If the amount of alkoxysilane to be blended is less than 0.1 parts by weight, the tensile strength of the PAS resin composition when made into a PAS resin composition is low, which is not preferable in practical use. Also, if the amount of alkoxysilane to be blended exceeds 10 parts by weight, the melt viscosity becomes significantly high, which is not preferable in terms of molding processing.
[0091] In the present invention, the adhesion between the PAS resin and the filler can be improved by forming a covalent bond between the PAS resin and the filler via a coupling agent. Examples of the covalent bond formed between the PAS resin and the filler include an ether bond, a urethane bond, an ester bond, an amide bond, an ester bond, an imide bond, and a urea bond. Among them, from the viewpoint of mold transferability, an ester bond formed by reaction of a carboxyl group of the PAS resin with an alkoxysilane having an epoxy group is preferred, and from the viewpoint of mechanical strength such as tensile strength, an amide bond formed by reaction with an alkoxysilane having an amino group, and a urethane bond formed by reaction with an alkoxysilane having an isocyanate group are preferred.
[0092] As a method for producing a PAS resin composition by mixing the PAS resin obtained in the present invention with a filler, production in a molten state or production in a solution state can be used, but from the viewpoint of simplicity, production in a molten state can be used. For production in a molten state, melt kneading using an extruder or melt kneading using a kneader can be used, but from the viewpoint of productivity, melt kneading using an extruder that can produce continuously can be used. For melt kneading using an extruder, one or more extruders such as a single screw extruder, a twin screw extruder, a multi-screw extruder such as a four-screw extruder, or a twin-screw single screw composite extruder can be used, but from the viewpoint of kneading property, reactivity, and productivity improvement, a multi-screw extruder such as a twin screw extruder or a four-screw extruder can be used preferably, and melt kneading using a twin screw extruder is most preferable.
[0093] In the present invention, moldability can be judged by the maximum molding pressure (molten resin pressure) at an injection time of 0.8 seconds when injection molding is performed using an ISO-A type mold conforming to ISO294. From the viewpoint of moldability, a lower molding pressure is more preferable. Here, the injection time refers to the time from the moment the screw starts moving forward until the injection process switches to the pressure holding process, and the molding pressure is the pressure applied to the plastic material at the tip of the screw during the injection time in the molding process.
[0094] The fluidity in the present invention can be evaluated by the spiral flow length. The longer the spiral flow length, the higher the fluidity. In general, the spiral flow length is preferably 100 mm or more, more preferably 120 mm or more, from the viewpoint of moldability. Moreover, from the viewpoint that resin leakage and burrs are easily generated when the fluidity is too high, the spiral flow length is preferably 300 mm or less.
[0095] Burrs can be evaluated by measuring the length of the burrs that occur in a gap of 10 μm width using a burr measurement mold. If there are many burrs, there is a problem of having to insert a process to remove them after molding, so it is better that there are no burrs, and the shorter the burr length, the better.
[0096] In the present invention, the tensile strength can be evaluated by a value obtained by using a JIS K7161-2 1A type test piece obtained by injection molding, using an AG-20kNx universal testing machine under conditions of a tensile speed of 5 mm / min, an atmospheric temperature of 23°C, and a relative humidity of 50%, according to ISO527-1 (2012). In the present invention, the lower limit of the tensile strength is preferably 150 MPa or more, more preferably 170 MPa or more, and even more preferably 180 MPa or more. If the tensile strength is less than 150 MPa, it is not practical and is not preferable as a molded product. In the present invention, there is no upper limit to the tensile strength, but it is usually less than 500 MPa.
[0097] [Uses of PAS resin composition] The PAS resin composition obtained by the present invention can be used not only for injection molding, injection compression molding and blow molding, but also for extrusion molding into extrusion molded products such as sheets, films, fibers and pipes.
[0098] Furthermore, the PAS resin composition of the present invention has excellent fluidity, low flash properties, and moldability, and is therefore useful for electrical and electronic parts, precision machinery parts, water-related parts, office equipment, automobile and vehicle parts, building materials, packaging materials, furniture, and daily miscellaneous goods, and is particularly useful for electrical and electronic parts, water-related parts, and automobile and vehicle parts. EXAMPLES
[0099] The method of the present invention will be explained in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0100] [Measurement of non-Newtonian indices] The PAS resin was pre-dried at 120°C for 4 hours under a nitrogen atmosphere, and then the shear rate and shear stress were measured using a capillograph at 320°C and capillary L / D = 10, and the non-Newtonian index N was calculated using the following formula. SR=K / SS N (where N is the non-Newtonian exponent, SR is the shear rate (S -1 ), SS is the shear stress (Pa), and K is a constant.
[0101] [Cyclic mass] The amount of cyclic substances in the PAS resin was calculated by the following method using high performance liquid chromatography (HPLC). The amount of cyclic substances referred to here refers to the total amount of cyclic substances having 4 to 14 repeating units.
[0102] Approximately 10 mg of PAS resin was dissolved in approximately 5 g of 1-chloronaphthalene at 250°C. When cooled to room temperature, a precipitate was formed. The 1-chloronaphthalene-insoluble components were filtered using a membrane filter with a pore size of 0.45 μm to obtain the 1-chloronaphthalene-soluble components. The amount of cyclic compounds was quantified by HPLC measurement of the obtained soluble components. The HPLC measurement conditions are as follows. Equipment: Shimadzu LC-10Avp series Column: Mightysil RP-18 GP150-4.6 (5 μm) Detector: photodiode array detector (UV=270 nm).
[0103] [Melt flow rate (MFR)] According to ASTM D 1238-70, the measurement was performed at a temperature of 315.5°C and a load of 5000g. A melt indexer manufactured by Toyo Seiki Co., Ltd. (length 8.00mm, orifice with a hole diameter of 2.095mm, sample amount 7g, preheat time from sample loading to measurement start 5 minutes, load 5kg) was used, and the measurement was performed under the condition of 315.5°C.
[0104] [Weight average molecular weight / dispersity (Mw / Mn) measurement] The weight average molecular weight Mw and the polydispersity (Mw / Mn) expressed as weight average molecular weight / number average molecular weight were calculated in terms of polystyrene by gel permeation chromatography (GPC), a type of size exclusion chromatography (SEC). The measurement conditions for GPC are shown below. Equipment: Senshu Science SSC-7110 Column name: Shodex UT806M x 2 Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL.
[0105] [Measurement of crystallization temperature during cooling] Using a TA DSCQ200 differential scanning calorimeter, the PAS resin was heated from 50°C to 340°C at a heating rate of 20°C / min under a nitrogen flow, held for 1 minute, and then cooled from 340°C to 100°C at a cooling rate of 20°C / min to measure the cooling crystallization temperature (Tmc) of the PAS resin.
[0106] [Creation of amorphous film] The conditions for producing the amorphous film were as follows: PAS resin and a spacer (aluminum plate of about 0.3 mm) were sandwiched between polyimide film. The polyimide film was sandwiched between a press mold heated to above the melting point of the PAS resin, and pressure was applied for one minute. After applying pressure for one minute to retain the PAS resin, the polyimide film was removed and immersed in prepared water to rapidly cool, yielding an amorphous film.
[0107] [Carboxyl group content] The carboxyl group content of the PAS resin was measured by measuring the amorphous film of the PAS resin with FT-IR (IR-810 infrared spectrophotometer manufactured by JASCO Corporation) and determining the 1,900 cm -1 The absorption at 1,730 cm originating from the carboxyl group -1 The absorption was estimated by comparing the absorption in the vicinity.
[0108] [Molding pressure] Using a Sumitomo Heavy Industries SE75-DUZ injection molding machine, molding was performed using an ISO-A type mold under conditions of resin temperature 310°C, mold temperature 160°C, injection time 0.8 seconds, cooling time 15 seconds, and injection speed 65mm / s. The maximum pressure applied to the nozzle during molding was recorded as the molding pressure.
[0109] [Spiral flow length] Using a spiral flow mold with a thickness of 1 mm (1 mmt), molding was performed under the conditions of a cylinder temperature of 320°C, a mold temperature of 140°C, an injection speed of 230 mm / sec, an injection pressure of 98 MPa, an injection time of 5 sec, and a cooling time of 15 sec, and the spiral flow length (unit: mm) was measured (injection molding machine used: Sumitomo Heavy Industries SE-30D).
[0110] [Bur measurement] Using a Sumitomo Heavy Industries injection molding machine (SE-30D), a 40 mm diameter x 3 mm thick disk-shaped mold having eight protrusions on the circumference, the following dimensions were used: (a) 5 mm wide x 20 mm long x 1,000 μm thick, (b) 5 mm wide x 20 mm long x 700 μm thick, (c) 5 mm wide x 20 mm long x 500 μm thick, (d) 5 mm wide x 20 mm long x 300 μm thick, (e) 5 mm wide x 20 mm long x 100 μm thick, (f) 5 mm wide x 20 mm long x 50 μm thick, (g) 5 mm wide x 20 mm long x 20 μm thick, and (h) 5 mm wide x 20 mm long x 10 μm thick, was used for injection molding under temperature conditions of a molding temperature of 320°C and a mold temperature of 130°C. The filling length of the protrusion (h) when the protrusion (b) was filled to the tip was measured, and this was taken as the burr length (mm). The gate was located at the center of the disk.
[0111] [Tensile strength] The tensile strength of the JIS K7161-2 1A type test pieces obtained by injection molding was measured in accordance with ISO527-1 using an AG-20kNx universal testing machine under conditions of a tensile speed of 5mm / min, an atmospheric temperature of 23°C, and a relative humidity of 50%, and the average value of five measurements was calculated.
[0112] [Synthesis Example 1] In an autoclave equipped with a stirrer and a bottom plug valve, 8.26 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.96 kg (70.70 mol) of 96% sodium hydroxide, 14.57 kg (147.00 mol) of N-methyl-2-pyrrolidone (NMP), 1.41 kg (17.5 mol) of sodium acetate, and 5.5 kg of ion-exchanged water were charged, and the mixture was gradually heated to 225°C over about 3 hours while passing nitrogen through it at normal pressure. When 9.84 kg of water and 0.28 kg of NMP were distilled, heating was stopped and cooling was started. At this point, the amount of hydrogen sulfide scattered was 1.4 mol, so the amount of sulfidizing agent in the system after this process was 68.6 mol.
[0113] Thereafter, the mixture was cooled to 200°C, and 10.12 kg (68.6 mol) of p-dichlorobenzene (p-DCB), 42 g (0.23 mol) of 1,2,4-trichlorobenzene (1,2,4-TCB), and 5.55 kg (56.0 mol) of NMP were added, after which the reaction vessel was sealed under nitrogen gas and heated from 200°C to 240°C at a rate of 0.6°C / min with stirring, and then heated from 240°C to 276°C at a rate of 0.8°C / min.
[0114] After reacting at 276°C for 123 minutes, the bottom plug valve of the autoclave was opened, and the contents were flushed into a vessel equipped with a stirrer over 15 minutes while pressurizing with nitrogen, and the contents were stirred at 250°C for a while to remove most of the NMP.
[0115] The obtained solid matter and 76 L of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70° C. for 30 minutes, and then suction filtered through a glass filter. Next, 76 L of ion-exchanged water heated to 70° C. was poured into the glass filter, and suction filtered to obtain a cake.
[0116] The obtained cake and 90 liters of ion-exchanged water were charged into an autoclave equipped with a stirrer, and acetic acid was added. After replacing the inside of the autoclave with nitrogen, the temperature was raised to 192°C and maintained for 30 minutes. The autoclave was then cooled and the contents were removed. The pH of the liquid after the acid treatment was 7.
[0117] The contents were filtered with a glass filter under suction, and then 76 liters of ion-exchanged water at 70° C. was poured therein and filtered under suction to obtain a cake. The obtained cake was dried at 120° C. under a nitrogen stream to obtain PPS.
[0118] The obtained dried PPS was placed in an autoclave equipped with a stirrer, 3.75 kg of NMP was added, and the mixture was stirred at 30°C for 20 minutes, after which it was suction filtered through a glass filter to obtain a cake. The obtained wet cake was dried at 220°C for 3 hours under a nitrogen stream to obtain a dried PPS. The properties of the obtained PPS were evaluated and the results are shown in Table 1.
[0119] [Synthesis Example 2] In an autoclave equipped with a stirrer and a bottom plug valve, 8.26 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.96 kg (70.70 mol) of 96% sodium hydroxide, 14.57 kg (147.00 mol) of N-methyl-2-pyrrolidone (NMP), 1.41 kg (17.5 mol) of sodium acetate, and 5.5 kg of ion-exchanged water were charged, and the mixture was gradually heated to 225°C over about 3 hours while passing nitrogen through it at normal pressure. When 9.84 kg of water and 0.28 kg of NMP were distilled, heating was stopped and cooling was started. At this point, the amount of hydrogen sulfide scattered was 1.4 mol, so the amount of sulfidizing agent in the system after this process was 68.6 mol.
[0120] Thereafter, the mixture was cooled to 200°C, and 10.12 kg (68.6) of p-dichlorobenzene (p-DCB), 42 g (0.23 mol) of 1,2,4-trichlorobenzene (1,2,4-TCB), and 5.55 kg (56.0 mol) of NMP were added, after which the reaction vessel was sealed under nitrogen gas and heated from 200°C to 240°C at a rate of 0.6°C / min with stirring, and then heated from 240°C to 276°C at a rate of 0.8°C / min.
[0121] After reacting at 276°C for 123 minutes, the bottom plug valve of the autoclave was opened, and the contents were flushed into a vessel equipped with a stirrer over 15 minutes while pressurizing with nitrogen, and the contents were stirred at 250°C for a while to remove most of the NMP.
[0122] The obtained solid matter and 76 L of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70° C. for 30 minutes, and then suction filtered through a glass filter. Next, 76 L of ion-exchanged water heated to 70° C. was poured into the glass filter, and suction filtered to obtain a cake.
[0123] The obtained cake and 90 liters of ion-exchanged water were charged into an autoclave equipped with a stirrer, and acetic acid was added. After replacing the inside of the autoclave with nitrogen, the temperature was raised to 192°C and maintained for 30 minutes. The autoclave was then cooled and the contents were removed. The pH of the liquid after the acid treatment was 7.
[0124] The contents were filtered through a glass filter under suction, and then 76 liters of 70°C ion-exchanged water was poured into it and filtered under suction to obtain a cake. The resulting cake was dried at 120°C under a nitrogen stream to obtain PPS. The properties of the resulting PPS were evaluated and the results are shown in Table 1.
[0125] [Synthesis Example 3] In an autoclave equipped with a stirrer and a bottom plug valve, 8.26 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.79 kg (72.80 mol) of 96% sodium hydroxide, 11.45 kg (115.50 mol) of N-methyl-2-pyrrolidone (NMP), 1.89 kg (23.10 mol) of sodium acetate, and 2.33 kg of ion-exchanged water were charged, and the mixture was gradually heated to 225°C over about 3 hours while passing nitrogen through it at normal pressure. When 9.71 kg of water and 0.25 kg of NMP were distilled, heating was stopped and cooling was started. At this point, the amount of hydrogen sulfide scattered was 1.4 mol, so the amount of sulfidizing agent in the system after this process was 68.6 mol.
[0126] After that, it was cooled to 200 ° C., 10.36 kg (70.45 mol) of p-dichlorobenzene (p-DCB) and 9.34 kg (94.50 mol) of NMP were added, and the reaction vessel was sealed under nitrogen gas, and the temperature was raised from 200 ° C. to 218 ° C. at a rate of 1.0 ° C. / min while stirring, and then the temperature was raised from 218 ° C. to 270 ° C. at a rate of 0.6 ° C. / min. After reacting at 270 ° C. for 140 minutes, it was cooled to 250 ° C. at a rate of 1.3 ° C. / min while injecting 1.26 kg of water over 15 minutes. Then, it was cooled to 200 ° C. at a rate of 0.4 ° C. / min, and then quenched to near room temperature.
[0127] The contents were taken out, washed twice with 40 kg of NMP, and then filtered under suction through a glass filter to obtain a cake.
[0128] The obtained cake and 76 liters of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70°C for 30 minutes, and then suction filtered through a glass filter. Next, 76 liters of ion-exchanged water heated to 70°C was poured into the glass filter, and suction filtered to obtain a cake.
[0129] The obtained cake and 90 liters of ion-exchanged water were charged into an autoclave equipped with a stirrer, and acetic acid was added. After replacing the inside of the autoclave with nitrogen, the temperature was raised to 192°C and maintained for 30 minutes. The autoclave was then cooled and the contents were removed. The pH of the liquid after the acid treatment was 4.
[0130] The contents were filtered through a glass filter under suction, and then 76 liters of ion-exchanged water at 70°C was poured into it and filtered under suction to obtain a cake. The resulting cake was dried at 120°C under a nitrogen stream to obtain a dried PPS. The properties of the resulting PPS were evaluated and the results are shown in Table 1.
[0131] [Synthesis Example 4] In an autoclave equipped with a stirrer and a bottom plug valve, 8.26 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.63 kg (68.53 mol) of 96% sodium hydroxide, 14.57 kg (147.00 mol) of N-methyl-2-pyrrolidone (NMP), 1.89 kg (23.1 mol) of sodium acetate, and 5.78 kg of ion-exchanged water were charged, and the mixture was gradually heated to 245°C over about 3 hours while passing nitrogen through it at normal pressure. When 9.70 kg of water and 0.28 kg of NMP were distilled, heating was stopped and cooling was started. The amount of hydrogen sulfide scattered at this point was 1.4 mol, so the amount of sulfidizing agent in the system after this process was 68.6 mol.
[0132] After that, the mixture was cooled to 200°C, 10.36 kg (70.45 mol) of p-dichlorobenzene (p-DCB) and 5.55 kg (56.00 mol) of NMP were added, and the reaction vessel was sealed under nitrogen gas. The mixture was heated from 200°C to 240°C at a rate of 0.6°C / min with stirring, and then heated from 240°C to 276°C at a rate of 0.8°C / min. After further reacting at 276°C for 75 minutes, the bottom plug valve of the autoclave was opened, and the contents were flushed into a vessel equipped with a stirrer over 15 minutes while pressurizing with nitrogen, and most of the NMP was removed by stirring for a while at 250°C.
[0133] The obtained solid matter and 76 L of ion-exchanged water were placed in an autoclave equipped with a stirrer, washed at 70° C. for 30 minutes, and then suction filtered through a glass filter. Next, 76 L of ion-exchanged water heated to 70° C. was poured into the glass filter, and suction filtered to obtain a cake.
[0134] The obtained cake and 90 liters of ion-exchanged water were charged into an autoclave equipped with a stirrer, and acetic acid was added. After replacing the inside of the autoclave with nitrogen, the temperature was raised to 192°C and maintained for 30 minutes. The autoclave was then cooled and the contents were removed. The pH of the liquid after the acid treatment was 7.
[0135] The contents were filtered with a glass filter under suction, and then 76 liters of ion-exchanged water at 70° C. was poured therein and filtered under suction to obtain a cake. The obtained cake was dried at 120° C. under a nitrogen stream to obtain PPS.
[0136] [Synthesis Example 5] The polyphenylene sulfide of Synthesis Example 4 was placed in a heating device equipped with a stirrer and subjected to heat treatment under conditions of an oxygen concentration of 2% and 200°C for 2 hours. The properties of the obtained PPS were evaluated, and the results are shown in Table 1.
[0137] [Synthesis Example 6] The polyphenylene sulfide of Synthesis Example 4 was placed in a heating device equipped with a stirrer and subjected to heat treatment under conditions of an oxygen concentration of 12% and 200°C for 4 hours. The properties of the obtained PPS were evaluated, and the results are shown in Table 1.
[0138] [Reference Example 1] Filler Filler-1: Glass fiber ("T760H" manufactured by Nippon Electric Glass Co., Ltd.).
[0139] [Reference Example 2] Alkoxysilane Alkoxysilane-1: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane ("KBM303" manufactured by Shin-Etsu Silicone Co., Ltd.)
[0140] [Example 1, Comparative Examples 1 to 4] As shown in Table 1, 100 parts by weight of the PAS resin obtained in each synthesis example was dry-blended with alkoxysilane in the ratio shown in Table 1, and then the mixture was melt-kneaded in a TEX30α type twin-screw extruder equipped with a vacuum vent (manufactured by Japan Steel Works, Ltd.: L / D=30, of the 11 cylinder blocks, the two in contact with the die tip were set to 300°C, and the remaining nine were set to 280°C (Tc: represents cylinder temperature). Furthermore, glass fiber was added as a filler from the side feeder of the twin-screw extruder in the ratio shown in Table 1. The gut obtained by melt-kneading was pelletized with a strand cutter and dried overnight at 130°C. The obtained resin composition pellets were subjected to injection molding, and the molding pressure, spiral flow length, and burr were measured. The results were as shown in Table 1.
[0141] [Table 1]
[0142] The results of the above-mentioned Examples and Comparative Examples will be compared and explained.
[0143] In Example 1, 100 parts by weight of polyarylene sulfide resin having a non-Newtonian index of 1.5 to 2.5, a carboxyl group content of 35 to 100 μmol / g, a cyclic content of 0.5 to 2.0 wt %, and a melt flow rate of 5 to 300 g / 10 min under conditions of 315.5°C and a load of 5,000 g was blended with 1 to 200 parts by weight of a filler and 0.1 to 10 parts by weight of an alkoxysilane having at least one functional group, thereby obtaining a PAS resin composition excellent in moldability, fluidity, flash suppression, and mold fouling suppression.
[0144] In contrast, in Comparative Example 1, cleaning with an organic polar solvent was not performed, and therefore the amount of cyclic bodies exceeded 2.0% by weight. As a result, a large amount of cyclic body components remained in the PAS resin, resulting in a PAS resin composition that had good fluidity but was poorly effective in suppressing burrs and could not suppress mold fouling.
[0145] In Comparative Example 2, the amount of cyclic bodies was 0.5 to 2.0% by weight, the melt flow rate was 315.5°C, and the load was 5,000 g, and the non-Newtonian index was less than 1.5 and the carboxyl group content was less than 35 μmol / g. Since the amount of cyclic bodies was small, mold contamination could be suppressed, but since the carboxyl group content was low, the interaction with coupling agents and fillers was low, resulting in a low-viscosity resin composition. However, since the non-Newtonian index of the resin was low, a PAS resin composition was obtained that had poor fluidity during molding and no effect of suppressing burrs.
[0146] In Comparative Example 3, the melt flow rate exceeded 300 g / 10 min under conditions of 315.5° C. and a load of 5000 g, the non-Newtonian index was less than 1.5, the carboxyl group content was less than 35 μmol / g, and the amount of cyclic substances exceeded 2.0 wt %. The low carboxyl group content resulted in low interaction with coupling agents and fillers, and the low non-Newtonian index of the resin itself resulted in a low non-Newtonian index when made into a resin composition, resulting in poor fluidity and a failure to achieve both a burr suppression effect and a mold fouling suppression effect.
[0147] In Comparative Example 4, the melt flow rate was 5 to 300 g / 10 min under conditions of 315.5°C and a load of 5000 g, but the non-Newtonian index was less than 1.5, the carboxyl group content was less than 35 μmol / g, and the amount of cyclic substances exceeded 2.0 wt%. The low carboxyl group content resulted in low interaction with coupling agents and fillers, and the large amount of cyclic substances gave good fluidity, but the low non-Newtonian index and low viscosity of the resin resulted in a PAS resin composition that had no effect of suppressing burrs or mold stains.
Claims
1. A polyarylene sulfide resin composition comprising 100 parts by weight of a polyarylene sulfide resin having a non-Newtonian index of 1.5 or more and 2.5 or less, a carboxyl group content of 35 μmol / g or more and 100 μmol / g or less, a cyclic content of 0.5% by weight or more and 2.0% by weight or less, and a melt flow rate measured under conditions of 315.5°C and a load of 5000 g of 5 g / 10 minutes or more and 300 g / 10 minutes or less, and a ...
2. 2. The polyarylene sulfide resin composition according to claim 1, wherein the polyarylene sulfide resin has a dispersity expressed by weight average molecular weight / number average molecular weight of 5.5 or more and 15.0 or less.
3. 2. The polyarylene sulfide resin composition according to claim 1, wherein the polyarylene sulfide resin has a weight average molecular weight of 60,000 or more and 150,000 or less.
4. The polyarylene sulfide resin composition according to claim 1, characterized in that the polyarylene sulfide resin has a temperature-decreasing crystallization temperature (Tmc) of 190°C or higher and 230°C or lower, measured at a temperature-decreasing rate of 20°C / min using a differential scanning calorimeter (DSC).
5. A molded article comprising the polyarylene sulfide resin composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Production of polyarylene sulfide
JP1990045532A
Fine particulate high branched type polyarylene sulfide and manufacturing method therefor, and high molecule modifier containing the polyarylene sulfide
JP2016108488A
Poly(arylene sulfide) and production method therefor
WO2021200332A1